Variations in vaccination uptake: COVID-19 vaccination rates in Swedish municipalities. - Elis Carlberg Larsson; Emanuel Wittberg; Susanne Wallman Lundåsen (Public Library of Science (PLoS), 2022)
Facing the threat of the ongoing COVID-19 pandemic, vaccines are important for limiting the spread and consequences of the pandemic. In this study, we provide a descriptive overview of the within-country variations of vaccine rates by examining to what extent voter turnout, support for an anti-establishment political party (Sweden Democrats), presence of first-generation immigrants, and Evangelical religiosity are associated with the within-country variation in vaccine uptake rates. We use official register data for municipality-level vaccine rates and municipality-level regressions with regional fixed effects. Our analyses show that vaccine uptake, on average, is lower in municipalities where the anti-establishment political party Sweden Democrats has higher vote shares and where a larger share of the population is first-generation immigrants. We discuss that potential explanations for these associations between vote shares for an anti-establishment party and shares of first-generation immigrants could be lower levels of trust in institutions and language barriers.